2008
DOI: 10.1111/j.1572-0241.2008.01743.x
|View full text |Cite|
|
Sign up to set email alerts
|

A 6-Thioguanine Nucleotide Threshold Level of 400 pmol/8 × 108Erythrocytes Predicts Azathioprine Refractoriness in Patients With Inflammatory Bowel Disease and Normal TPMT Activity

Abstract: A 6-TGN level of >400 pmol/8 x 10(8) erythrocytes in IBD patients with normal TPMT activity and steroid-dependent or active disease despite an optimal AZA regimen may predict refractoriness to this drug. Furthermore, high levels of methylated derivatives are associated with an increased risk of myelotoxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(16 citation statements)
references
References 26 publications
1
15
0
Order By: Relevance
“…The HGPRT activity was measured in 20,000 g diluted supernatant, as described earlier. 26,27 Final substrate concentrations were 1.86 mM 5-phosporibosyl-1-pyrophosphate (PRPP) (Sigma-Aldrich Corp., St. Louis, MO, USA), with (18-28 μg protein per assay) and 0.15 mM [8][9][10][11][12][13][14] C] hypoxanthine (47 mCi/mmol, Moravek Biochemicals Inc., Brea, CA, USA).…”
Section: Hypoxanthine-guanine Phosphoribosyl Transferase (Hgprt)mentioning
confidence: 99%
See 1 more Smart Citation
“…The HGPRT activity was measured in 20,000 g diluted supernatant, as described earlier. 26,27 Final substrate concentrations were 1.86 mM 5-phosporibosyl-1-pyrophosphate (PRPP) (Sigma-Aldrich Corp., St. Louis, MO, USA), with (18-28 μg protein per assay) and 0.15 mM [8][9][10][11][12][13][14] C] hypoxanthine (47 mCi/mmol, Moravek Biochemicals Inc., Brea, CA, USA).…”
Section: Hypoxanthine-guanine Phosphoribosyl Transferase (Hgprt)mentioning
confidence: 99%
“…High 6-MMPR concentrations are associated with toxicity, in particular hepatotoxicity but even with myelotoxicity, whereas 6-TGN concentrations above a certain cut-off (N 235 mmol/8 × 10^8 RBC) are associated with therapeutic efficacy. [5][6][7][8] However, prospective studies have not be able to demonstrate that 6-TGN-guided dosing is superior to Scheme of the thiopurine metabolism Figure 1 Following conversion of azathioprine (AZA) into 6-mercaptopurine (6MP), the first step in bioactivation of 6MP is mediated by hypoxanthine-guanine phosphoribosyl transferase (HGPRT) and yields 6-thioinosine monophosphate (6TIMP). However, 6MP can also be oxidized by xanthine oxidase (XO) into inactive 6-thiouric acid (6TUA), or methylated by thiopurine S-methyl transferase (TPMT) into 6-methyl mercaptopurine (6MMP).…”
Section: Introductionmentioning
confidence: 99%
“…IBD studies have demonstrated that 6‐TGN levels are higher in patients in disease remission compared with those with active disease 5, 8–10 . Measuring serial 6‐TGN levels during dose escalation may be used to induce remission of disease by achieving therapeutic levels, while minimizing risk of toxicity 8, 11 . Studies suggest that a lower limit of 235–260 pmol/8 × 10 8 RBC is desirable 5, 8, 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Myelosuppression occurrence is strongly linked to high 6‐TGN blood levels and low TPMT activity 80, 81, 98, 136 . Indeed, 6‐TGN intra‐erythrocyte levels represent an indirect biomarker of 6‐TGN accumulation into bone marrow, which results in myelotoxicity 97, 124, 137 . Patients with reduced or undetectable TPMT activity, due to genetic alterations, exhibit a preferential metabolism towards 6‐TGN through HPRT pathway and consequently are predisposed to bone marrow suppression 18, 127, 128, 138, 139 .…”
mentioning
confidence: 99%